2005
DOI: 10.1007/bf03166755
|View full text |Cite
|
Sign up to set email alerts
|

The first observation of electron spin polarization in the excited triplet states caused by the triplet-triplet annihilation

Abstract: The spin polarization of excited triplet states caused by mutual annihilation of triplet states was detected by time-resolved EPR of triplet excitons in two molecular crystals, anthracene/tetracyanobenzene and phenazine/TCNQ. The time profile of the two EPR lines of the triplet exciton spectrum have been studied in the time range up to 200 s after a laser pulse. Besides the initial polarization of the lines, due to inter system crossing, a long-lasting polarization process is detected, which is attributed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
0
11
1
Order By: Relevance
“…[32] On the other hand, the triplet-triplet-annihilation process could cause electron spin polarization, which further amplifies the magnetic-dipole transition moment (m gn ), which would be positive for the increase of g lum values. [36,154] The amplified magnetic-dipole transition moment and depressed electric-dipole moments resulted in the increase of CPL g lum in the TTA-UC system.…”
Section: Photon Upconversion Based On Triplet-triplet Annihilationmentioning
confidence: 99%
See 1 more Smart Citation
“…[32] On the other hand, the triplet-triplet-annihilation process could cause electron spin polarization, which further amplifies the magnetic-dipole transition moment (m gn ), which would be positive for the increase of g lum values. [36,154] The amplified magnetic-dipole transition moment and depressed electric-dipole moments resulted in the increase of CPL g lum in the TTA-UC system.…”
Section: Photon Upconversion Based On Triplet-triplet Annihilationmentioning
confidence: 99%
“…On the one hand, it is proposed that CPL can be achieved by populating the emitting state indirectly, either by inter‐ or intramolecular radiationless energy transfer, which could significantly influence the μ gn with a negative effect . On the other hand, the triplet–triplet‐annihilation process could cause electron spin polarization, which further amplifies the magnetic‐dipole transition moment ( m gn ), which would be positive for the increase of g lum values . The amplified magnetic‐dipole transition moment and depressed electric‐dipole moments resulted in the increase of CPL g lum in the TTA‐UC system.…”
Section: Strategies For the Enhancement Of Cplmentioning
confidence: 99%
“…It has been demonstrated that the μ gn could be significantly decreased in radiationless energy transfer process,[1b] which may account for the amplification of g lum in TTA‐UC systems. In addition, the perturbation of m gn in the TTA‐UC process is negligible, because the TTA‐UC process would result in a triplet state pool, and spin polarization of electron could be caused by the paramagnetic triplet state, which would be a positive factor to the dipole transition moment. In the end, the depressed electric dipole moments and electron spin polarization together would significantly enhance g lum .…”
Section: Amplification Of Cpl Through Tta‐based Photon Upconversionmentioning
confidence: 99%
“…For readers’ convenience, I present a selected list of my publications dealing with the main topics of my long-term research: spin chemistry [ 1 22 ]; pulse EPR spectroscopy [ 23 – 38 ]; spin exchange [ 39 – 52 ]; and diverse publications [ 53 59 ].…”
Section: My Future Plansmentioning
confidence: 99%